2014
DOI: 10.1007/s00330-014-3365-9
|View full text |Cite
|
Sign up to set email alerts
|

High-pitch computed tomography pulmonary angiography with iterative reconstruction at 80 kVp and 20 mL contrast agent volume

Abstract: CTPA is feasible at 80 kVp using only 20 ml of contrast agent. High-pitch CTPA at 80 kVp has an effective dose under 1 mSv. This CTPA protocol can obtain sufficient image quality in normal-weight individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
87
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 31 publications
2
87
2
Order By: Relevance
“…Lu et al attempted to reduce both the radiation dose and the amount of contrast material in CT pulmonary angiography (CTPA) simultaneously [15]. Low tube voltage (80 kVp) and a high-pitch technique were employed.…”
Section: The Predicament: Radiation Exposurementioning
confidence: 99%
“…Lu et al attempted to reduce both the radiation dose and the amount of contrast material in CT pulmonary angiography (CTPA) simultaneously [15]. Low tube voltage (80 kVp) and a high-pitch technique were employed.…”
Section: The Predicament: Radiation Exposurementioning
confidence: 99%
“…This has been widely reported in cardiovascular CT imaging, such as coronary CT angiography, [21][22][23][24] abdominal aortic imaging, 25,26 and CTPA. [27][28][29][30] Similarly, CIN has been drawing more attention in the recent literature due to routine use of contrast medium injection during CT scans including CTPA. Thus, reduction of contrast medium volume is equally important as reduction of radiation dose, which is shown in some studies.…”
mentioning
confidence: 99%
“…Their results showed significant improvement in the visualization of pulmonary vessels with use of low contrast medium. Another study by Lu et al 30 reported their experience of further lowering the contrast medium to 20 ml with tube voltage of 80 kVp and high-pitch protocol. Of 100 patients with suspected pulmonary embolism, 50 patients were scanned with the CTPA protocol of 100 kVp, pitch of 1.2 and 60 ml of contrast medium, while another 50 patients with the protocol of 80 kVp, pitch of 2.2 and 20 ml of contrast.…”
mentioning
confidence: 99%
See 2 more Smart Citations